KEPUASAN MAHASISWA PROGRAM STUDI KOMUNIKASI DAN PENYIARAN ISLAM TERHADAP PELAYANAN ADMINISTRASI AKADEMIK FAKULTAS DAKWAH INSTITUT AGAMA ISLAM NEGERI PURWOKERTO TAHUN 2017 - Muridan Muridan (IAIN Purwokerto, 2017)
Abstract: Students are customers in higher education institutions. It is said as customer because they pay for education services to get study. This must be accompanied by desirable expectations in the educational process. Such as service, facilities, lecturer quality, and leadership. Research on student satisfaction is expected to be a reference to conduct evaluation and improvement at the level of institutions and study programs. This research is a survey research with quantitative descriptive. The population in this research is all students of Islamic Communication Studies and Broadcasting Program of IAIN Purwokerto. Of this population, then taken a representative sample of 15%. The sample in this study amounted to 40 respondents. Aspects of physical evidence services or elements of tangibles in the form of educational facilities - lecture tools, instructional media, educational infrastructure and departmental activities that support student learning given by the Faculty of Dakwah quite satisfactory. On the aspect of Reliability or reliability of lecturers and Academic staff, it is quite satisfactory with the reliability of lecturers and academic staff. Aspects of responsiveness (Attitude responsiveness) that Attitude is given by the faculty of Da'wah considered quite satisfaction. Aspects of Assurance (treatment on students) shows that the responsiveness or Aspects of Responsiveness provided by the faculty of Dakwah quite satisfaction. Keywords: Quality of Administration Service, Academic, Satisfaction, student